Glorifier of russian aggression: criminological characteristics of a person who commits a criminal offense under Article 4362 of the Criminal Code of Ukraine - Kopcha, V.V. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article is devoted to forming a criminological portrait of a person committing a criminal offense under Article 4362 of the Criminal Code of Ukraine in the form of justification, recognition as lawful, denial of the Russian Federation’s armed aggression against Ukraine, and glorification of its participants. The author emphasizes that the relevance of such research in the context of ongoing Russian aggression and growing information threats becomes critical for national security, as glorifiers of Russian aggression objectively perform the function of a hostile propaganda tool, weaken the unity of Ukrainian society, and spread destructive narratives. The article analyzes a complex of socio-demographic, criminal-legal, and moral-psychological characteristics of glorifiers. The author indicates that the analysis of official statistics and empirical research of court verdicts allows forming a portrait of a typical glorifier of Russian aggression. This is a Ukrainian citizen of middle or older age with basic education who has not previously been prosecuted. The vast majority of such persons do not have permanent employment, which contributes to social isolation and increased susceptibility to propaganda. Special attention in the article is focused on the psychological phenomenon of «Stockholm syndrome» at the national level, when certain categories of Ukrainian citizens have Soviet narratives so deeply rooted in their consciousness that they perceive Ukraine’s independence as an anomaly. It was found that glorifiers of Russian aggression are characterized by information isolation, low level of critical thinking, distorted legal consciousness, and susceptibility to manipulation. The author indicates that the elderly are a particularly vulnerable group, who, due to loneliness, easily fall victim to disinformation on social networks. The author concludes that the criminological portrait of a glorifier of Russian aggression reflects a combination of social vulnerability, low legal culture, and media literacy, which requires the development of specific criminological prevention measures to counter information threats in wartime.